ANALISIS TINGKAT KEPUASAN PELANGGAN TERHADAP PELAYANAN PT PELNI (PERSERO) - Rohman, Arif Fatkur; Syairudin, Bambang; Angreni, Endah (Universitas Nahdlatul Ulama Surabaya, 2018)
Development and competition business of transporting had been restrictive. Each operators race competition do innovation, efficiency, and continuous improvement. The customers of PT Pelni from year to year continues to decrease. Although actually PT Pelni also improve themselves, repair service and innovation, but still be unable to improve the number of passengers. This study attempts to know the level customer satisfaction PT Pelni to make known well and innovation that has done is in line with hope customers. The measurement of the customer satisfaction PT Pelni done with the approach servqual method. Aspects which are under consideration includes 5 dimensions main namely tangibles, reliability, responsiveness, assurance, and empathy which divided in 29 indicators variable. This research using respondents as the sample. Data analysis used the analysis method servqual and cartesious diagrams. The research results show that there are inconquirity between hope customers by the fact experienced. The largest is in dimension tangible, with the gap an average of -1,3.While gap smallest there are in dimension responsiveness -0,42. Analysis by diagram cartecious show you some attribute in the main priority improvement: furnishings that high quality (2), facilities shopping centers on a vessel (4), the availability of a bed with the corresponding numbers of a ticket (6), size cabin large (7), and the condition a clean room (8). All those attributes including in dimension of tangible.